Reproducibility assessment of the Lauge-Hansen classification for ankle fractures - Prata, Sérgio Damião Santos; Farias, Fábio; Rizzo, Marco Antônio; Soares, Ruan Dalbem; Silveira, Fabio Duque (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the reproducibility, among orthopaedists, of the Lauge-Hansen classification performed at two different times, with an understanding of the trauma mechanism in each type of fracture. Methods: Thirty radiographs of ankle fractures were selected for assessment by five orthopaedists from our service, two of whom were already trained and three of whom were undergoing orthopaedic residency training. Results: The results were tabulated and plotted, and in a second assessment after 1 week, 66% correct answers and 34% errors were found. In the first assessment, the percentage of correct answers was 61.33%. Conclusion: Management of the classification makes the orthopaedists habituated to using it routinely, facilitating the understanding by other professionals in the field and reducing disagreement among observers. Level of Evidence III; Retrospective Comparative Study.